2006
DOI: 10.1038/sj.bmt.1705350
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, reproduction and sexuality after stem cell transplantation with partially T-cell-depleted grafts and after conditioning with a regimen including total body irradiation

Abstract: Thirty-four men and 36 women (median age 43 and 45 years, respectively) underwent stem cell transplantation (SCT) for acute leukaemia in first complete remission or chronic myelogenous leukaemia in first chronic phase between 1981 and 2001 from HLA-identical siblings. The conditioning regimen included TBI and all grafts were partially depleted of T cells. Changes in quality of life (QOL), reproduction and sexuality were studied using a questionnaire, and the previously given information related to these proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
2
32
0
1
Order By: Relevance
“…This finding is consistent with previous studies that have examined sexual functioning specifically [7][8][9][10] or as part of a larger quality of life assessment in BMT recipients. [1][2][3][4][5][6] Compared to a previous study 10 of sexual functioning that included baseline, 1-and 3-year time points, our participants reported more sexual difficulties pretransplantation in terms of orgasm (14 vs 46% for women; 4 vs 13% for men) vaginal dryness (30 vs 49%), erectile dysfunction (13 vs 33%) and painful intercourse for women (14 vs 29%). At year 1, women in the current study reported significantly more problems compared to the previous study in terms of difficulties with orgasm (24 vs 72%), vaginal dryness (49 vs 78%) and painful intercourse (35 vs 61%).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies that have examined sexual functioning specifically [7][8][9][10] or as part of a larger quality of life assessment in BMT recipients. [1][2][3][4][5][6] Compared to a previous study 10 of sexual functioning that included baseline, 1-and 3-year time points, our participants reported more sexual difficulties pretransplantation in terms of orgasm (14 vs 46% for women; 4 vs 13% for men) vaginal dryness (30 vs 49%), erectile dysfunction (13 vs 33%) and painful intercourse for women (14 vs 29%). At year 1, women in the current study reported significantly more problems compared to the previous study in terms of difficulties with orgasm (24 vs 72%), vaginal dryness (49 vs 78%) and painful intercourse (35 vs 61%).…”
Section: Discussionmentioning
confidence: 93%
“…Quality of life studies have shown that sexual dysfunction and dissatisfaction are frequently reported among BMT patients, although with varying rates. [1][2][3][4][5][6] Despite the apparent prevalence of sexual issues in BMT survivors, there have been few longitudinal studies examining sexual functioning in this population. Most studies of sexual functioning have used short follow-up periods (3-12 months) or have been cross-sectional in nature.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][22][23][24][25][26][27][28][29][30][31] The majority of these, 4 each, came from the United States and the United Kingdom, 2 from Germany and 1 each from Canada, Ireland, The Netherlands and Finland.…”
Section: Resultsmentioning
confidence: 99%
“…6,[22][23][24][25][27][28][29] Five studies were prospective designs, with follow-up periods from 1 to 10 years. 6,8,9,27,30 Case-matched controls were used in four studies.…”
Section: Research Design and Purposesmentioning
confidence: 99%
“…13 In spite of improved techniques and new drug invention in recent years, HSCT is still a procedure that is associated with high rate of morbidity and mortality. GVHD, 14 hypothyroidism, 15 cataract, 16 veno-occlusive disorder, 17 interstitial pneumonia, 18 hemorrhagic cystitis 19 and decrement of the quality of life 20 are the most common post-HSCT complications. It is believed that the conditioning regimen plays a crucial role in the development of these complications.…”
Section: Introductionmentioning
confidence: 99%